Saturday

August 23, 2014

August 23, 2014

Posted by **Corin** on Friday, May 4, 2007 at 12:26am.

1.) sinxcosx+sinx^3secx=tanx

2.) (secx+tanx)/(secx-tan)=(secx+tanx)^2

I tried starting from the left on both problems, but am stuck.

like I said before, change everything into sines and cosines.

for the first one:

LS= sinxcosx + (sin^3x)cosx

=(sinxcos^2x + sin^3x)/cosx

=

=

factor out the sinx, and look what you have left inside the bracket!

two more steps!

the second one is just as easy.

LS = (1/cosx + sinx/cosx)(1/cosx - sinx/cosx)

=

=

can you see the common factor, and the difference of squares pattern?

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Math - I can't find the integral for (tanx)^(6)*(secx)^(2) I tried splitting up ...

math - 1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Trig - Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x...

Math - Im really struggling with these proving identities problems can somebody ...

Pre-Calculus - How can this identity be proved/verified? cscx-sinx=1/(secxtanx) ...

Trig - Verify the identity. 1/(tanx-secx) + 1/(tanx+secx) = -2tanx

Trig - Verify that each of the following is an identity. tan^2x-sin^2x=tan^2xsin...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...